The water we eat – tackling scarcity in ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2011)
The rate at which we consume water has grown twice as fast as the world population over the last 100 years, and many countries regularly experience water scarcity. The Brussels Development Briefing on ‘The Water We Eat’ highlighted the measures required if future generations are to make sustainable use of finite global water supplies. This CTA Policy Brief covers the following topics: natural resources and environment, economics and policy, and food security. Policy pointers include giving priority to increasing productivity in areas used for rain-fed agriculture, implementing a cross-sectoral approach, promoting the involvement of farmers’ groups to improve water governance and encouraging investment to improve access to water.